Correlation between emotional acceptance of parents and independence level of adolescents - V. V. Kozyreva; V.A.T. Pham (Вестник университета)
The article considers the formation of independence in adolescents under the influence of emotional acceptance from parents in Vietnam and Russia. Parental emotional acceptance helps teenagers gain self-confidence and avoid difficulties when they make decisions and solve problems, thereby developing independence in thinking and behaviour. Using the methodologies “Behaviour of parents and the attitude of adolescents to them” by E. Shafer and “Diagnostics of students’ independence” by L.A. Sergienko, the authors analyse the correlation between emotional acceptance from influential parents and the level of a teenager’ autonomy. In addition, the influence of fathers and mothers on the independence of adolescents is different. The results show that emotional acceptance from both parents helps teenagers develop autunomy better than emotional acceptance from just one person. Besides, the level of emotional support is higher among Russian parents than among Vietnamese ones, and this leads to the fact that Russian teenagers are more independent than Vietnamese ones. Emotional acceptance from parents plays an important role in the development of autonomy in children, therefore parents need to create healthy relationships with them.